Predicting the impact of management and climate scenarios on groundwater nitrate concentration trends in southern Portugal - Costa, Luis (2021)
The dynamics related to evolution of nitrate-contaminated groundwater are analyzed with focus on the impact of intrinsic aquifer properties, agricultural activities and restoration measures at Campina de Faro aquifer (M12), southern Portugal. Agricultural practices in the region developed in the 1970s and resulted in high abstraction rates, nitrate contamination and salinization. Despite the implementation of the European Union (EU) Nitrates Directive since 1997, nitrate levels still show increasing trends at some locations, constituting a threat to the chemical status of M12 and consequent nitrate discharge to Ria Formosa coastal lagoon. Simultaneously, groundwater levels are not dropping consistently, despite apparent overexploitation. A groundwater flow and mass transport model is developed for M12 to assess the evolution of nitrate under different scenarios. Model results reveal that M12 has a hydraulic connection with northernmost aquifers, a process not properly assessed so far. Results further show that nitrate contamination in the upper Plio-Quaternary layer of M12 is extremely persistent and mostly linked to unbalanced fertilizer application practices and irrigation return flows. The response of M12 to implementation of good agricultural practices in compliance with EU policies is slow, indicating that good qualitative status would be impossible to reach by the required EU deadlines. Integration of climate change scenarios into the transport model reveals that despite the implementation of restoration measures, there could be a retardation of the nitrate levels' decrease in the upper aquifer as a result of enhanced evapoconcentration caused by lower recharge, higher water demands and incomplete mixing within the aquifer.